Pengembangan Virtual Reality Sebagai Media Pembelajaran Sistem Tata Surya - Darojat, Muhammad Abid; Ulfa, Saida; Wedi, Agus (Universitas Negeri Malang, 2022)
This research and development aims to produce a product in the form of virtual reality development media as a learning medium for the solar system on the material of the solar system. Thisresearch Research and Development (R&D) uses the Sadiman method, which stages are in accordance with the product to be developed. The sadiman method has several stages such as needs analysis, formulation of learning objectives, formulation of material, formulation of measuring tools for success, preparation of media scripts, media production, validation, ready-to-use media. In this virtual reality media learning is used as a complement to teaching materials for science subjects. The results of the product feasibility test that have been carried out on media experts, material experts, and students have received many positive responses, so it can be concluded that the media virtual reality system of the solar system is suitable for use in learning. This media makes it easy for students to analyze the arrangement of the solar system and provides an attraction for students so that an increased sense of desire to learn arises. However, to use it, you must use a device that already has the capability of a gyroscopeAbstrakPenelitian dan pengembangan ini bertujuan untuk menghasilkan produk berupa media pengembangan virtual reality sebagai media pembelajaran sistem tata surya pada materi susunan tata surya. Penelitian Research and Development (R&D) ini menggunakan metode Sadiman yang tahapannya sesuai dengan produk yang akan dikembangkan. Metode sadiman memiliki beberapa tahapan seperti analisis kebutuhan, perumusan tujuan pembelajaran, perumusan materi, perumusan alat ukur keberhasilan, penyusunan naskah media, produksi media, validasi, media siap pakai. Didalam pembelajaran media virtual reality ini digunakan sebagai pelengkap bahan ajar untuk mata pelajaran IPA. Hasil dari uji kelayakan produk yang telah dilaksanakan pada ahli media, ahli materi, dan siswa mendapatkan banyak tanggapan positif, sehingga dapat disimpulkan bahwa media virtual reality system tata surya ini layak digunakan dalam pembelajaran. Media ini memberikan kemudahan pada siswa dalam menganalisa susunan tata surya dan memberikan daya tarik untuk siswa sehingga timbul rasa ingin belajar yang meningkat. Akan tetapi untuk penggunaannya harus menggunakan gawai yang sudah memiliki kemampuan gyroscope.